Sequential effects in continued visual search: Using fixation-related potentials to compare distractor processing before and after target detection - Körner, Christof; Braunstein, Verena; Stangl, Matthias; Schlögl, Alois; Neuper, Christa; Ischebeck, Anja (Psychophysiology)
To search for a target in a complex environment is an everyday behavior that ends with finding the target. When we search for two identical targets, however, we must continue the search after finding the first target and memorize its location. We used fixation-related potentials to investigate the neural correlates of different stages of the search, that is, before and after finding the first target. Having found the first target influenced subsequent distractor processing. Compared to distractor fixations before the first target fixation, a negative shift was observed for three subsequent distractor fixations. These results suggest that processing a target in continued search modulates the brain's response, either transiently by reflecting temporary working memory processes or permanently by reflecting working memory retention.

Y-linked Mendelian inheritance of giant and dwarf male morphs in shell-brooding cichlids - Ocana, Sabine; Meidl, Patrick; Bonfils, Danielle; Taborsky, Michael (Proceedings of the Royal Society of London Series B Biological Sciences)
Behavioural variation among conspecifics is typically contingent on individual state or environmental conditions. Sex-specific genetic polymorphisms are enigmatic because they lack conditionality, and genes causing adaptive trait variation in one sex may reduce Darwinian fitness in the other. One way to avoid such genetic antagonism is to control sex-specific traits by inheritance via sex chromosomes. Here, controlled laboratory crossings suggest that in snail-brooding cichlid fish a single locus, two-allele polymorphism located on a sex-linked chromosome of heterogametic males generates an extreme reproductive dimorphism. Both natural and sexual selection are responsible for exceptionally large body size of bourgeois males, creating a niche for a miniature male phenotype to evolve. This extreme intrasexual dimorphism results from selection on opposite size thresholds caused by a single ecological factor, empty snail shells used as breeding substrate. Paternity analyses reveal that in the field parasitic dwarf males sire the majority of offspring in direct sperm competition with large nest owners exceeding their size more than 40 times. Apparently, use of empty snail shells as breeding substrate and single locus sex-linked inheritance of growth are the major ecological and genetic mechanisms responsible for the extreme intrasexual diversity observed in Lamprologus callipterus.

Deterministic progenitor behavior and unitary production of neurons in the neocortex - Gao, Peng; Postiglione, Maria P; Krieger, Teresa; Hernandez, Luisirene; Wang, Chao; Han, Zhi; Streicher, Carmen; Papusheva, Ekaterina; Insolera, Ryan; Chugh, Kritika; Kodish, Oren; Huang, Kun; et al. (Cell)
Radial glial progenitors (RGPs) are responsible for producing nearly all neocortical neurons. To gain insight into the patterns of RGP division and neuron production, we quantitatively analyzed excitatory neuron genesis in the mouse neocortex using Mosaic Analysis with Double Markers, which provides single-cell resolution of progenitor division patterns and potential in vivo. We found that RGPs progress through a coherent program in which their proliferative potential diminishes in a predictable manner. Upon entry into the neurogenic phase, individual RGPs produce ∼8–9 neurons distributed in both deep and superficial layers, indicating a unitary output in neuronal production. Removal of OTX1, a transcription factor transiently expressed in RGPs, results in both deep- and superficial-layer neuron loss and a reduction in neuronal unit size. Moreover, ∼1/6 of neurogenic RGPs proceed to produce glia. These results suggest that progenitor behavior and histogenesis in the mammalian neocortex conform to a remarkably orderly and deterministic program.

Stimfit: Quantifying electrophysiological data with Python - Guzmán, José; Schlögl, Alois; Schmidt Hieber, Christoph (Frontiers in Neuroinformatics)
Intracellular electrophysiological recordings provide crucial insights into elementary neuronal signals such as action potentials and synaptic currents. Analyzing and interpreting these signals is essential for a quantitative understanding of neuronal information processing, and requires both fast data visualization and ready access to complex analysis routines. To achieve this goal, we have developed Stimfit, a free software package for cellular neurophysiology with a Python scripting interface and a built-in Python shell. The program supports most standard file formats for cellular neurophysiology and other biomedical signals through the Biosig library. To quantify and interpret the activity of single neurons and communication between neurons, the program includes algorithms to characterize the kinetics of presynaptic action potentials and postsynaptic currents, estimate latencies between pre- and postsynaptic events, and detect spontaneously occurring events. We validate and benchmark these algorithms, give estimation errors, and provide sample use cases, showing that Stimfit represents an efficient, accessible and extensible way to accurately analyze and interpret neuronal signals.

Invasive parasites habitat change and heavy rainfall reduce breeding success in Darwin's finches - Cimadom, Arno; Ulloa, Angel; Meidl, Patrick; Zöttl, Markus; Zöttl, Elisabet; Fessl, Birgit; Nemeth, Erwin; Dvorak, Michael; Cunninghame, Francesca; Tebbich, Sabine (PLoS One)
Invasive alien parasites and pathogens are a growing threat to biodiversity worldwide, which can contribute to the extinction of endemic species. On the Galápagos Islands, the invasive parasitic fly Philornis downsi poses a major threat to the endemic avifauna. Here, we investigated the influence of this parasite on the breeding success of two Darwin's finch species, the warbler finch (Certhidea olivacea) and the sympatric small tree finch (Camarhynchus parvulus), on Santa Cruz Island in 2010 and 2012. While the population of the small tree finch appeared to be stable, the warbler finch has experienced a dramatic decline in population size on Santa Cruz Island since 1997. We aimed to identify whether warbler finches are particularly vulnerable during different stages of the breeding cycle. Contrary to our prediction, breeding success was lower in the small tree finch than in the warbler finch. In both species P. downsi had a strong negative impact on breeding success and our data suggest that heavy rain events also lowered the fledging success. On the one hand parents might be less efficient in compensating their chicks' energy loss due to parasitism as they might be less efficient in foraging on days of heavy rain. On the other hand, intense rainfalls might lead to increased humidity and more rapid cooling of the nests. In the case of the warbler finch we found that the control of invasive plant species with herbicides had a significant additive negative impact on the breeding success. It is very likely that the availability of insects (i.e. food abundance) is lower in such controlled areas, as herbicide usage led to the removal of the entire understory. Predation seems to be a minor factor in brood loss.

Notes from Research Data Alliance Plenary Meeting in Dublin, Ireland - Porsche, Jana
Notes from the Third Plenary for the Research Data Alliance in Dublin, Ireland on March 26 to 28, 2014 with focus on starting an institutional research data repository.

Linked (Open) Data - Bibliographische Daten im Semantic Web - Danowski, Patrick; Goldfarb, Doron; Schaffner, Verena; Seidler, Wolfram (VÖB Mitteilungen)
Linked (Open) Data - bibliographic data on the Semantic Web. Report of the Working Group on Linked Data to the plenary assembly of the Austrian Library Network (translation of the title). Linked Data stands for a certain approach to publishing data on the Web. The underlying idea is to harmonise heterogeneous data sources of different origin in order to improve their accessibility and interoperability, effectively making them queryable as a big distributed database. This report summarises relevant developments in Europe as well as the Linked Data Working Group‘s strategic and technical considerations regarding the publishing of the Austrian Library Network’s (OBV’s) bibliographic datasets. It concludes with the mutual agreement that the implementation of Linked Data principles within the OBV can only be taken into consideration accompanied by a discussion about the provision of the datasets under a free license.

(Open) Linked Data in Bibliotheken - Danowski, Patrick; Pohl, Adrian
Das Buch ist sowohl eine Einführung in die Themen Linked Data, Open Data und Open Linked Data als es auch den konkreten Bezug auf Bibliotheken behandelt. Hierzu werden konkrete Anwendungsprojekte beschrieben. Der Band wendet sich dabei sowohl an Personen aus der Bibliothekspraxis als auch an Personen aus dem Bibliotheksmanagement, die noch nicht mit dem Thema vertraut sind.

Complete genome sequence of the novel phage MG-B1 infecting bacillus weihenstephanensis - Fernandes Redondo, Rodrigo A; Kupczok, Anne; Stift, Gertraud; Bollback, Jonathan P (Genome Announcements)
Here, we describe a novel virulent bacteriophage that infects Bacillus weihenstephanensis, isolated from soil in Austria. It is the first phage to be discovered that infects this species. Here, we present the complete genome sequence of this podovirus.

Interstitial dendritic cell guidance by haptotactic chemokine gradients - Weber, Michele; Hauschild, Robert; Schwarz, Jan; Moussion, Christine; De Vries, Ingrid; Legler, Daniel; Luther, Sanjiv; Bollenbach, Mark Tobias; Sixt, Michael K (Science)
Directional guidance of cells via gradients of chemokines is considered crucial for embryonic development, cancer dissemination, and immune responses. Nevertheless, the concept still lacks direct experimental confirmation in vivo. Here, we identify endogenous gradients of the chemokine CCL21 within mouse skin and show that they guide dendritic cells toward lymphatic vessels. Quantitative imaging reveals depots of CCL21 within lymphatic endothelial cells and steeply decaying gradients within the perilymphatic interstitium. These gradients match the migratory patterns of the dendritic cells, which directionally approach vessels from a distance of up to 90-micrometers. Interstitial CCL21 is immobilized to heparan sulfates, and its experimental delocalization or swamping the endogenous gradients abolishes directed migration. These findings functionally establish the concept of haptotaxis, directed migration along immobilized gradients, in tissues.

Initiatives and projects related to RD - Porsche, Jana
This document is created as a part of the project “Repository for Research Data at IST Austria”. It summarises the actual initiatives, projects and standards related to the project. It supports the preparation of standards and specifications for the project, which should be considered and followed to ensure interoperability and visibility of the uploaded data.

Technical requirements and features - Porsche, Jana
This document is created as a part of the project “Repository for Research Data at IST Austria”. It summarises the mandatory features, which need to be fulfilled to provide an institutional repository as a platform and also a service to the scientists at the institute. It also includes optional features, which would be of strong benefit for the scientists and would increase the usage of the repository, and hence the visibility of research at IST Austria.

A deconvolution based method with high sensitivity and temporal resolution for detection of spontaneous synaptic currents in vitro and in vivo - Pernia-Andrade, Alejandro; Goswami, Sarit; Stickler, Yvonne; Fröbe, Ulrich; Schlögl, Alois; Jonas, Peter M (Biophysical Journal)
Spontaneous postsynaptic currents (PSCs) provide key information about the mechanisms of synaptic transmission and the activity modes of neuronal networks. However, detecting spontaneous PSCs in vitro and in vivo has been challenging, because of the small amplitude, the variable kinetics, and the undefined time of generation of these events. Here, we describe a, to our knowledge, new method for detecting spontaneous synaptic events by deconvolution, using a template that approximates the average time course of spontaneous PSCs. A recorded PSC trace is deconvolved from the template, resulting in a series of delta-like functions. The maxima of these delta-like events are reliably detected, revealing the precise onset times of the spontaneous PSCs. Among all detection methods, the deconvolution-based method has a unique temporal resolution, allowing the detection of individual events in high-frequency bursts. Furthermore, the deconvolution-based method has a high amplitude resolution, because deconvolution can substantially increase the signal/noise ratio. When tested against previously published methods using experimental data, the deconvolution-based method was superior for spontaneous PSCs recorded in vivo. Using the high-resolution deconvolution-based detection algorithm, we show that the frequency of spontaneous excitatory postsynaptic currents in dentate gyrus granule cells is 4.5 times higher in vivo than in vitro.

Forces driving epithelial spreading in zebrafish gastrulation - Behrndt, Martin; Salbreux, Guillaume; Campinho, Pedro; Hauschild, Robert; Oswald, Felix; Roensch, Julia; Grill, Stephan; Heisenberg, Carl-Philipp J (Science)
Contractile actomyosin rings drive various fundamental morphogenetic processes ranging from cytokinesis to wound healing. Actomyosin rings are generally thought to function by circumferential contraction. Here, we show that the spreading of the enveloping cell layer (EVL) over the yolk cell during zebrafish gastrulation is driven by a contractile actomyosin ring. In contrast to previous suggestions, we find that this ring functions not only by circumferential contraction but also by a flow-friction mechanism. This generates a pulling force through resistance against retrograde actomyosin flow. EVL spreading proceeds normally in situations where circumferential contraction is unproductive, indicating that the flow-friction mechanism is sufficient. Thus, actomyosin rings can function in epithelial morphogenesis through a combination of cable-constriction and flow-friction mechanisms.

Kontext Open Access: Creative Commons - Danowski, Patrick (Mitteilungen der Vereinigung Österreichischer Bibliothekarinnen & Bibliothekare)
Dieser Artikel soll die sechs verschiedenen Creative Commons Lizenzen erläutern und ihre Bedeutung im Rahmen des wissenschaftlichen Publizierens und des Open Access erklären (CC-BY, CC-BY-SA, CC-BY-NC, CC-BY-ND, CC-BYNC-SA, CC-BY-NC-ND).

Review of the BCI competition IV - Tangermann, Michael; Müller, Klaus; Aertsen, Ad; Birbaumer, Niels; Braun, Christoph; Brunner, Clemens; Leeb, Robert; Mehring, Carsten; Miller, Kai; Müller Putz, Gernot; Nolte, Guido; Pfurtscheller, Gert; et al. (Frontiers in Neuroscience)
The BCI competition IV stands in the tradition of prior BCI competitions that aim to provide high quality neuroscientific data for open access to the scientific community. As experienced already in prior competitions not only scientists from the narrow field of BCI compete, but scholars with a broad variety of backgrounds and nationalities. They include high specialists as well as students.The goals of all BCI competitions have always been to challenge with respect to novel paradigms and complex data. We report on the following challenges: (1) asynchronous data, (2) synthetic, (3) multi-class continuous data, (4) sessionto-session transfer, (5) directionally modulated MEG, (6) finger movements recorded by ECoG. As after past competitions, our hope is that winning entries may enhance the analysis methods of future BCIs.

Actual state of research data @ ISTAustria - Porsche, Jana
This document is created as a part of the project “Repository for Research Data on IST Austria”. It summarises the actual state of research data at IST Austria, based on survey results. It supports the choice of appropriate software, which would best fit the requirements of their users, the researchers.

Die Zeit des Abwartens ist vorbei! - Danowski, Patrick (BuB - Forum Bibliothek und Information)
Bibliothekare haben die Aufgabe, sich mit neuen Medienformen auseinanderzusetzen.

Zwischen Technologie und Information - Danowski, Patrick (Büchereiperspektiven)
Wie wandelt sich das Berufsbild in Wissenschaftlichen Bibliotheken? Patrick Danowski gibt seine Einschätzung ab.

BioSig: The free and open source software library for biomedical signal processing - Schlögl, Alois; Vidaurre, Carmen; Sander, Tilmann (Computational Intelligence and Neuroscience)
BioSig is an open source software library for biomedical signal processing. The aim of the BioSig project is to foster research in biomedical signal processing by providing free and open source software tools for many different application areas. Some of the areas where BioSig can be employed are neuroinformatics, brain-computer interfaces, neurophysiology, psychology, cardiovascular systems, and sleep research. Moreover, the analysis of biosignals such as the electroencephalogram (EEG), electrocorticogram (ECoG), electrocardiogram (ECG), electrooculogram (EOG), electromyogram (EMG), or respiration signals is a very relevant element of the BioSig project. Specifically, BioSig provides solutions for data acquisition, artifact processing, quality control, feature extraction, classification, modeling, and data visualization, to name a few. In this paper, we highlight several methods to help students and researchers to work more efficiently with biomedical signals.

Ilastik: Interactive learning and segmentation toolkit - Sommer, Christoph M; Straehle, Christoph; Köthe, Ullrich; Hamprecht, Fred A. (2011 IEEE International Symposium on Biomedical Imaging: from Nano to Micro)
Segmentation is the process of partitioning digital images into meaningful regions. The analysis of biological high content images often requires segmentation as a first step. We propose ilastik as an easy-to-use tool which allows the user without expertise in image processing to perform segmentation and classification in a unified way. ilastik learns from labels provided by the user through a convenient mouse interface. Based on these labels, ilastik infers a problem specific segmentation. A random forest classifier is used in the learning step, in which each pixel's neighborhood is characterized by a set of generic (nonlinear) features. ilastik supports up to three spatial plus one spectral dimension and makes use of all dimensions in the feature calculation. ilastik provides realtime feedback that enables the user to interactively refine the segmentation result and hence further fine-tune the classifier. An uncertainty measure guides the user to ambiguous regions in the images. Real time performance is achieved by multi-threading which fully exploits the capabilities of modern multi-core machines. Once a classifier has been trained on a set of representative images, it can be exported and used to automatically process a very large number of images (e.g. using the CellProfiler pipeline). ilastik is an open source project and released under the BSD license at www.ilastik.org.
Keywords: image segmentation; biomedical imaging; three dimensional displays; neurons; retina; observers; image color analysis

Handbuch Bibliothek 2.0
With the term "Library 2.0" the editors mean an institution which applies the principles of the Web 2.0 such as openness, re-use, collaboration and interaction in the entire organization. Libraries are extending their service offerings and work processes to include the potential of Web 2.0 technologies. This changes the job description and self-image of librarians. The collective volume offers a complete overview of the topic Library 2.0 and the current state of developments from a technological, sociological, information theoretical and practice-oriented perspective.

Spatial organization of adhesion: force-dependent regulation and function in tissue morphogenesis - Papusheva, Ekaterina; Heisenberg, Carl-Philipp J (EMBO Journal)
Integrin- and cadherin-mediated adhesion is central for cell and tissue morphogenesis, allowing cells and tissues to change shape without loosing integrity. Studies predominantly in cell culture showed that mechanosensation through adhesion structures is achieved by force-mediated modulation of their molecular composition. The specific molecular composition of adhesion sites in turn determines their signalling activity and dynamic reorganization. Here, we will review how adhesion sites respond to mecanical stimuli, and how spatially and temporally regulated signalling from different adhesion sites controls cell migration and tissue morphogenesis.

Ist Bibliothek 2.0 überhaupt noch relevant? – Eine Einleitung in das Handbuch - Bergmann, Julia; Danowski, Patrick (Handbuch Bibliothek 2.0)
Mit diesem Buch möchten wir einen Überblick der aktuellen Diskussion zum Thema Bibliothek 2.0 geben und den Stand der tatsächlichen Umsetzung der Web 2.0-Ansätze in deutschsprachigen Bibliotheken beleuchten. An dieser Stelle ist die Frage erlaubt, warum es zu einer Zeit, in der es bereits die ersten "Web 3.0"- Konferenzen gibt, eines Handbuches der Bibliothek 2.0 noch bedarf. Und warum es überhaupt ein deutschsprachiges Handbuch zur Bibliothek 2.0 braucht, wo es doch bereits verschiedenste Publikationen zu diesem Thema aus anderen Ländern, insbesondere des angloamerikanischen Raums gibt. Ist dazu nicht bereits alles gesagt?

Adaptive Methods in BCI Research - An Introductory Tutorial - Schlögl, Alois; Vidaurre, Carmen; Müller, Klaus-Robert (Brain-Computer Interfaces)
This chapter tackles a difficult challenge: presenting signal processing material to non-experts. This chapter is meant to be comprehensible to people who have some math background, including a course in linear algebra and basic statistics, but do not specialize in mathematics, engineering, or related fields. Some formulas assume the reader is familiar with matrices and basic matrix operations, but not more advanced material. Furthermore, we tried to make the chapter readable even if you skip the formulas. Nevertheless, we include some simple methods to demonstrate the basics of adaptive data processing, then we proceed with some advanced methods that are fundamental in adaptive signal processing, and are likely to be useful in a variety of applications. The advanced algorithms are also online available [30]. In the second part, these techniques are applied to some real-world BCI data.